Illocutionary Acts Used By Newt Scamander In Fantastic Beast (The Crimes Of Grindelwald) Movie Script - Qani’ah, Binti; Agustina, Syarifah Rini (CV. ITTC INDONESIA, 2024)
This study examined the illocutionary acts performed by Newt Scamander, the main character in the Fantastic Beast (The Crimes of Grindelwald) movie script, with the aims of identifying the types and explaining the meaning of the illocutionary acts performed by the main character. This study employed George Yule's (1996) theory of illocutionary acts. The descriptive-qualitative method was used for this study. This study discovered 114 illocutionary acts spoken by the main character in the Fantastic Beast (The Crimes of Grindelwald) movie. There were 59 representatives data, 32 directives data, 15 expressives data, 6 commissives data, and 2 declaratives data. Newt was a person who likes to speak the truth rather than express feelings. In this movie, Newt had the ambition to prevent conflict, so he rarely expressed himself. He more often expressed existing facts and opinions.